Factors Predicting Safety Culture Among Nurses in Tertiary Care Hospitals - Pakamas Boonyaphisompan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Safety culture is crucial for patient safety as it can facilitate harm reduction in healthcare setting and the improvement of care quality and safety. This predictive study aimed to examine the level of safety culture among nurses working at tertiary care hospitals as well as to determine the predictability of safety culture among unit experience, nurse working hours, management safety commitment, structural empowerment, and work engagement. The study sample, randomly selected, were 471 nurses working at four tertiary care hospitals in Thailand. The research instruments were questionnaires which were reviewed for quality and confirmed by experts. These included the Hospital Survey on Patient Safety Culture (HSOPSC), the Managers’ Safety Commitment Scale (MSCS), The Gallup Q12 Employee Engagement Survey, and the Thai version of Conditions of Work Effectiveness Questionnaire-II (CWEQ-II). Data were analyzed using descriptive statistics and stepwise multiple regression. The major findings indicated that composites which considered as the areas of strength or good levels included feedback and communication about errors (92.63%), and organizational learning continuous improvement (89.57%), teamwork within units (78.25%), and management support for safety culture (75.47%), while those considering as areas needing improvement or weak levels were the frequency of events reported v (44.20%), staffing (40.70%), and non-punitive response to errors (38.93%). Structural empowerment, management safety commitment, work engagement, and nurse working hours could explain 33 percent of the variance in safety culture among nurses in tertiary care hospitals. The results of this study thus provide scientific evidence for either hospitals or nurse administrators to highlight an active reporting system for adverse events, in particular non-punitive responses to errors. Further, managing staffing for patient safety appropriately needs to be implemented. Effective strategies for improving safety culture need to take essence elements of structural empowerment, management safety commitment, work engagement, and nursing workload into consideration.